Oral Health Education of Staff in Long-Term Care Institutions - Petrovski Mihajlo; Terzieva-Petrovska Olivera; Kovecevska Ivona; Minovska Ana; Ivanovski Kiro; Papakoca Kiro (Balkan Stomatological Society, 2019)
Creating of protocol for the education for oral health and improving oral hygiene among institutionalized elderly is of great significance in prevention of the consequences that can provide numerous oral diseases among the elderly. Activation of as much as possible range of professionals in the field of dentistry in creation of this protocol and the fundamentals for the education of dental staff, and other professionals who care for health also has great significance. In this way with minimal financial loss will be reached maximum benefit-improved quality of life for institutionalized elderly. Taking into consideration the previously mentioned facts about of oral health, the presence of numerous dental problems and increased health needs and poor health among institutionalized elderly the aim of this paper was made- to make a draft protocol for education of the staff responsable for care of the institutionalized elderly aged over 65 years. In this paper are presented fundamentals of a proposed protocol for improving of oral health and hygiene among institutionalized elderly. Presented are all disadvantages in of oral health care for the elderly, are given directions and goals in order for improving of oral health and hygiene among the elderly, guidelines and targets for prevention programs to educate the professionals who care for them.